Lattice expansion in Rb-doped hybrid organic-inorganic perovskite crystals resulting in smaller band-gap and higher light-yield scintillators - Maddalena, Francesco (2023)
Two-dimensional hybrid-organic-inorganic perovskite (2D-HOIP) lead bromide perovskite crystals have demonstrated great potential as scintillators with high light yields and fast decay times while also being low cost with solution-processable materials for wide energy radiation detection. Ion doping has been also shown to be a very promising avenue for improvements of the scintillation properties of 2D-HOIP crystals. In this paper, we discuss the effect of rubidium (Rb) doping on two previously reported 2D-HOIP single crystals, BA2PbBr4 and PEA2PbBr4. We observe that doping the perovskite crystals with Rb ions leads to an expansion of the crystal lattices of the materials, which also leads to narrowing of band gaps down to 84% of the pure compounds. Rb doping of BA2PbBr4 and PEA2PbBr4 shows a broadening in the photoluminescence and scintillation emissions of both perovskite crystals. Rb doping also leads to faster γ-ray scintillation decay times, as fast as 4.4 ns, with average decay time decreases of 15% and 8% for Rb-doped BA2PbBr4 and PEA2PbBr4, respectively, compared to those of undoped crystals. The inclusion of Rb ions also leads to a slightly longer afterglow, with residual scintillation still being below 1% after 5 s at 10 K, for both undoped and Rb-doped perovskite crystals. The light yield of both perovskites is significantly increased by Rb doping with improvements of 58% and 25% for BA2PbBr4 and PEA2PbBr4, respectively. This work shows that Rb doping leads to a significant enhancement of the 2D-HOIP crystal performance, which is of particular significance for high light yield and fast timing applications, such as photon counting or positron emission tomography.